Viabilidad de Comercialización de Pulpa de Fruta para Canadá - Montilla Marmolejo, Oscar Mauricio (Universidad Antonio Nariño, 2021)
This project begins as a concern, based on how to be able to export more and better through innovation, focusing on the export of fruits and the search for a blue ocean. The problem of the thesis arises when we ask the following question: How to enter in the export of Colombian fruit pulp in an innovative way? From here it follows each of its objectives. The main objective was to set aside the export of commodities and generate value added with a good value proposition for the target market and the general market. For this, it is decided to work with processed and combined fruit pulp, which mixtures not only arouse feelings and emotions, but additionally, they provide well-being to the consumers of this product. After conducting the market research study, in search of a viable country for this product, we get as a result Canada. This is because the profile of its population combined with the profile of the project, meet the needs of the market of this country, finding in this an unexplored niche but with a strong need for health and well-being